2016
DOI: 10.1177/1535370216660215
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on coagulation and fibrinolysis factors in patients with peripheral arterial disease

Abstract: Peripheral arterial disease is a widely prevalent atherosclerotic occlusive disorder. Symptoms commence with exercise-induced pain in the lower extremities, known as claudication. Despite the fact that exercise has been shown to improve fibrinolytic profile some patients, the effect of exercise on coagulation and fibrinolysis cascades in claudicants has not been comprehensively defined. Literature search in English language yielded 13 studies of exercise on claudicants, including 420 patients. Claudicants tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Yes (Womack et al, 2003) Uncertain (Patelis et al, 2016) Yes (Comerota et al, 1997) No Effect (Arora et al, 2005) (Ahlbom et al, 2016) 36% compared to standing, <2 METS (Fares et al, 2016) N/A 12-15% in both supine and seated posture. No change at end of JD.…”
Section: Biochemical Effectmentioning
confidence: 99%
“…Yes (Womack et al, 2003) Uncertain (Patelis et al, 2016) Yes (Comerota et al, 1997) No Effect (Arora et al, 2005) (Ahlbom et al, 2016) 36% compared to standing, <2 METS (Fares et al, 2016) N/A 12-15% in both supine and seated posture. No change at end of JD.…”
Section: Biochemical Effectmentioning
confidence: 99%
“…The decreased levels of TXB2 might also reflect a lower synthesis of its precursor, thromboxane A2, which is involved in platelet activation and aggregation [ 31 ]. Accordingly, this could reflect the improved fibrinolytic profile induced by regular training [ 32 ]. We further demonstrated that 18-HEPE was found at higher concentrations in the plasma of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa kejadian kematian saat melakukan olahraga sering terjadi pada pagi hari yaitu sekitar pukul 09.00 -10.00 (Szymanski & Pate, 1994). Selain menurunkan risiko serangan jantung, olahraga sore dapat meningkatkan aktivitas fibrinolisis sehingga menurunkan viskositas darah (Szymanski & Pate, 1994;Patelis, Karaolanis, Kouvelos, Hart, Metheiken, 2016 (de Oliveira & Burini, 2011;Moses, 1990).…”
Section: Waktu Latihan Atau Berolahraga Terbaikunclassified